Foster Care Being a Second Home for Abandoned Children: An Analysis on Cathy Glass’s Saving Danny. - T , Chaamili Swetha G.; Jaisre, V. (International Journal of Membrane Science and Technology, 2023)
This paper explores the role of foster care as a secondary home for abandoned children and its significance in fulfilling the developmental needs of these youngsters. As biological parents seek support, recovery, and therapy, foster care offers a secure refuge for children and adolescents. Abuse and neglect often necessitate the removal of children and teenagers from their homes, making it imperative to find a secure environment for them. Foster care serves as a refuge for children and teenagers in need, even though it might be challenging to perceive it as a stable environment at first glance. The act of uprooting children from their homes may seem unsettling, but for those who have experienced abuse or neglect, foster care offers a stable and supportive home setting. Foster families provide essential elements like education, meals, shelter, and access to healthcare, which these children may have lacked before entering foster care. This, in turn, positively impacts their physical, mental, and emotional well-being. Additionally, foster care can provide biological parents with an opportunity to focus on establishing a stable home environment where their children can eventually return. This research draws inspiration from Cathy Glass’s "Saving Danny," a powerful narrative. Cathy Glass is a prolific author with a portfolio of 34 books, each of which offers valuable insights into the lives of children in foster care. Through the lens of Cathy’s experiences as a foster carer, these stories shed light on the challenges these vulnerable children face and how a nurturing and loving environment can help them overcome these obstacles.